Application of Circular Economy in Sustainable Supply Chain Management in the Fashion Industry - Kirono, Catur Sasi; Sono, Mohammad Gifari (Westscience Press, 2025)
This study examines the integration of circular economy (CE) principles within sustainable supply chain management (SSCM) in the fashion industry through a systematic review of 35 Scopus-indexed documents. The findings reveal that CE strategies, such as recycling, upcycling, and product life extension, are increasingly adopted to reduce waste and promote resource efficiency. Sustainable sourcing, green manufacturing, and efficient logistics are identified as critical SSCM activities supporting circular practices. However, challenges such as economic barriers, technological gaps, and consumer awareness hinder widespread adoption. The study highlights the importance of policy support, collaborative efforts, and technological advancements as enablers of CE implementation. Comparative insights from other industries further underscore the potential for scalable and innovative circular practices in fashion. These findings provide actionable recommendations for practitioners, policymakers, and researchers to enhance sustainability in the fashion industry's supply chains.